THE USE OF AIRCRFAT NATIONALITY AND REGISTRATION MARKS ADAPTED BY ANNEX 7 INTERNATIONAL CIVIL AVIATION ORGANIZATION (ICAO) - Assyifa Azzahra; Adya Paramita Prabandari; Pulung Widhi Hari Hananto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2025)
This study discusses the use of aircraft registration codes and nationality marks according to ICAO Annex 7 and their legal impacts if violations occur. This study emphasizes the importance of compliance with regulations to ensure flight safety, security, and accountability and provides theoretical and practical contributions in understanding and implementing international aircraft registration rules. The study analyzes violations by foreign aircraft serving domestic routes in Indonesia without valid registration, violating ICAO Annex 7 and national law. This study emphasizes the importance of compliance with regulations to ensure flight safety, security, and accountability and provides theoretical and practical contributions in understanding and implementing international aircraft registration rules